CONCEPTUAL MODEL FOR ASSESSING THE CHANNEL CHANGES UPSTREAM FROM DAM RESERVOIR - Liro, Maciej (Quaestiones Geographicae, 2014)
Most of geomorphological studies related to the impact of dam reservoirs are focused on its effect on the river channels downstream of dams. However, little is known about the evolution of river channels upstream of dams (in backwater areas). In this paper I propose a conceptual model of alluvial channel changes in the backwater. It assumes that three conditions of a channel that may occur in the pre-dam period. These are sediment supply deficit, balance and surplus compared to the river transport capacity. These conditions can be strengthened, stable or weakened. In the post-dam period these conditions is modified by the influence of the dam reservoir, which may affect the trajectory of channel changes, as well as its response and adjustment time in the backwater. The adjustment of channel parameters, in spite of the reservoir operation mode, also depends on the local river, reach characteristics and the magnitude and frequency of floods. Therefore, the use of an appropriate reference reach is inherent in this model. The model suggests that some adverse changes to backwater channels degraded by the regulation can be hampered. The model is based on Lane’s balance concept. It may be useful for explaining and predicting channel changes upstream of reservoirs and forming hypotheses in other studies.